TESTING OF DEVIATIONS OF PATE FILLING SYSTEM USING PARETO METHOD (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The main goal of this research study was to find the causes of the deviation system for filling chicken pate in samples of different weights, with 27 g and 45 g. By applying the recognized methods of determining the level of process control for the calculation of the potential index (Cp) and the capacity index (Cpk) of the process, it was necessary to determine whether the filling process is under control. The research was performed in the plant for the production of chicken pate, and the samples needed for the research were collected on the technological line for the production of chicken pate, at the process steps for filling and closing. Samples were taken from the filling line periodically at intervals of 30 minutes to 60 minutes. For each group, 500 measurements were performed over a period of several days depending on the production plan for a given group of samples. The results of the research show that the examined filling processes in both groups meet the requirements on filling quantities prescribed by the Internal Regulations, as well as the EU Directive on prepacked products (76/211 / EEC, ANEX 1) and (75/106 / EEC). Calculations of process ability indicators indicated that according to the values of Cp and Cpk index (precision and adjustment), the process of filling 27 g of chicken pate belongs to the group of precise and adjusted process, while the process of filling 45 g of chicken pate belongs to the group of precise but unadjusted processes. CpU and CpL centering indicators indicate the non-centering of both processes, i.e. the measured values in both, group I and group II go towards the upper limit of the specifications. The results showed in the first process there is no defect at all, so there are no measured values outside the specifications, while in the second process the percentage of defects is 31.4%. Determining the causes of deviation using the Pareto method indicated the fact that overload dosing, lack of weight in the dosing can and damage to the packaging cause the largest number of defects (89.5%).